(untitled) (Bangladesh Journal of Psychiatry, 2019)
Alice in wonderland syndrome is a phenomenon of perceptual distortion where individual experiences wrong sense of body image which is often associated with depersonalization and/ or derealization. A case of a late adult stroke patient with distorted visual perception regarding his hands and legs was depicted here. The patient’s concern of asymmetry in his body parts were only abolished by practical evidence to the contrary though the events continued to come about repeatedly. Reassurance with evidence was added with stroke management as no other specific treatment was available. Further diverse epidemiolocal studies were suggested to execute and publish highlighting the management of this syndrome. Bang J Psychiatry 2019; 33(2): 32-33